Problems, politics, and policy streams in policy implementation. Issue 3 (21st December 2018) - Fowler, Luke
Abstract : We apply Kingdon's multiple streams framework (MSF) to policy implementation to reflect a nested process separate from but interdependent with policymaking. Then, we generate a hypothesis concerning the conditional nature of problems, policies, and politics stream impacts on policy implementation. We test our hypotheses with state‐level implementation of the Clean Air Act, Clean Water Act, and Resource Conservation and Recovery Act, using a pooled data set of 10 years of toxic releases data. Findings suggest an important interaction occurs among problems, policies, and politics during the policy implementation process. More specifically, when any of the three is held at median levels, only marginal differences in outputs occur; however, when all three are increased to extreme levels, substantive differences emerge. Conclusions connect policy implementation to larger issues of MSF theoretical development and suggest implications for governance.